2018
DOI: 10.1017/pasa.2018.47
|View full text |Cite
|
Sign up to set email alerts
|

Supernova lightCURVE POPulation Synthesis I: Including interacting binaries is key to understanding the diversity of type II supernova lightcurves

Abstract: We present results of a supernova light-curve population synthesis, predicting the range of possible supernova lightcurves arising from a population of progenitor stars that include interacting binary systems. We show that the known diversity of supernova lightcurves can be interpreted as arising from binary interactions. Given detailed models of the progenitor stars, we are able to the determine what parameters within these stars determine the shape of their supernova lightcurve. The primary factors are the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 56 publications
1
46
0
2
Order By: Relevance
“…This is particularly important if the binary fraction is high (Zapartas et al 2019). Additionally, Eldridge et al (2018) find that SN II-P like light curves can be produced from RSGs with M fin ∼ 4M , and that stellar mergers can produce RSGs with M fin ∼ 40M . For single stars, there is a much narrower expected range of final masses.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This is particularly important if the binary fraction is high (Zapartas et al 2019). Additionally, Eldridge et al (2018) find that SN II-P like light curves can be produced from RSGs with M fin ∼ 4M , and that stellar mergers can produce RSGs with M fin ∼ 40M . For single stars, there is a much narrower expected range of final masses.…”
Section: Discussionmentioning
confidence: 90%
“…Our models predict that for a star to be a RSG at the end of its evolution (assuming T eff < 5000 K), it must have M env of 0.1−0.5M , depending on the value of M He-core . Eldridge et al (2018) found that the minimum hydrogen mass required to produce a SN II-P is 1M . RSGs with M env of ∼ 0.1 − 1M may produce SN II-L when they explode.…”
Section: Discussionmentioning
confidence: 99%
“…For massive stars, the main sequence phase is followed by the red supergiant phase, which is dominated by slow, dense winds, with velocities of ∼ 10-20 km s −1 and mass loss rates of ∼ 0.5-2.0 × 10 −5 M yr −1 (Smith 2014). While there are currently large uncertainties about the mass loss rates of RSGs based on observations (Georgy 2017), it is believed that most of the progenitor's mass is lost during the RSG phase, which lasts for 1.0 Myr (Eldridge et al 2018). The RSG wind expands into the low density main sequence wind, eventually forming a wind-blown, radiatively cooled shell.…”
Section: Cas A's Progenitor Mass-loss Historymentioning
confidence: 99%
“…However, there are few studies that focus on a quantitative comparison of light-curve morphologies between SNe II and SNe IIb (c.f. : Arcavi et al 2012, Faran et al 2014, Eldridge et al 2018).…”
mentioning
confidence: 99%